A Single Chip Standalone Water Splitting Photoelectrochemical Cell - Frites, Mourad; Jr., William B. Ingler; Khan, Shahed U.M. (Journal of Technology Innovations in Renewable Energy, 2014)
Water splitting photoelectrochemical cell (PEC) was fabricated in which the electrolyzer parts were made on a single chip. This was achieved by depositing an optically transparent Mn-oxide-TiO2 thin layer on the front of a triple junction amorphous Si photovoltaic cell which acted as the anode and the back stainless steel layer acted as the cathode under illumination of light. This single chip water electrolysis cell operates like an artificial leaf. Water splitting was observed by simply submersing the device in a basic electrolyte solution under solar simulated light of 1 sun (0.1 W cm-2). This self-driven PEC was found to produce hydrogen gas at the rate of 12.42 L m-2 h-1 and a solar to hydrogen efficiency (STHE) of 3.25 % from the collected H2 gas in 2.5 M KOH solution. No signs of degradation of this single chip PEC were observed during water splitting when the device was run continuously for 6 hours.